Implementation of Cultural Internalization Through Effective Communication Training as an Effort to Increase Work Motivation at Hospital - Agus Aan Adriansyah; Budhi Setianto; Akas Yekti Pulih Asih; Yauwan Tobing Lukiyono; Nikmatus Sa’adah (PROSIDING SEMINAR NASIONAL PENGABDIAN KEPADA MASYARAKAT, 2024)
The addition of new buildings and services at hospitals The millennial generation is now starting to dominate the world of work. This condition is a challenge for agencies in managing human resource (HR) management strategies because the generation gap presents differences in ways of working, perspectives and ways of communicating. With this gap, training is held regarding effective communication so that there are no differences in communication between gap generations. This training aims to intervene in the implementation of culture as an effort to increase work motivation. The training was attended by 64 structural officials using lectures, discussions and case studies. This training, which was packaged attractively and attended enthusiastically by the participants, has provided benefits to the participants. shows the final test on the data is higher than the initial test. However, the range of distribution of final test data also becomes smaller, this shows that there is an increase in knowledge regarding effective communication. The following are Paired sample correlations to test the influence related to the implementation of Cultural Internalization Implementation Training with Effective Communication Training at Hospital X as an Effort to Increase Work Motivation